Confinement-guided photophysics in MOFs, COFs, and cages. (17th February 2021) - Leith, Gabrielle A.; Martin, Corey R.; Mayers, Jacob M.; Kittikhunnatham, Preecha; Larsen, Randy W.; Shustova, Natalia B.
Abstract : This review applies a holistic approach for recognizing a pattern in the photophysics–structure relationship of chromophore in porous crystalline matrices. Abstract : In this review, the dependence of the photophysical response of chromophores in the confined environments associated with crystalline scaffolds, such as metal–organic frameworks (MOFs), covalent-organic frameworks (COFs), and molecular cages, has been carefully evaluated. Tunability of the framework aperture, cavity microenvironment, and scaffold topology significantly affects emission profiles, quantum yields, or fluorescence lifetimes of confined chromophores. In addition to the role of the host and its effect on the guest, the methods for integration of a chromophore ( e.g., as a framework backbone, capping linker, ligand side group, or guest) are discussed. The overall potential of chromophore-integrated frameworks for a wide-range of applications, including artificial biomimetic systems, white-light emitting diodes, photoresponsive devices, and fluorescent sensors with unparalleled spatial resolution are highlighted throughout the review.